The Influence of Computer Use and Information Technology Literacy on Enhancing the Abilities of College Students at the Nahdlatul Ulama Institute of Technology and Science Lampung - Maisaroh Maisaroh; Dewi Puspitasari (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
This study aims to determine the effect of computer use and understanding of information technology on improving the abilities of students in the Information Technology Study Program at the Nahdlatul Ulama Lampung Institute of Technology and Science. The main problem identified is the still low utilization of practical computer technology in the learning process, even though universities have made large investments in providing facilities. This study uses a qualitative approach with a data collection method through a questionnaire distributed to 102 students from the 2021 to 2024 intake. The results showed that most students preferred practice-based learning methods to theory, and more than half of respondents used computers or laptops in their daily activities. In addition, most students already had basic knowledge of technology, information, hardware, software, and networks before entering college. The conclusion of this study is that educational background, experience using computers, and practice-based learning methods significantly affect the improvement of students' abilities in the field of information technology. These findings reinforce the importance of implementing practice-based learning methods and optimizing computer laboratory facilities in order to produce graduates who are ready to compete in the digital era.